Honeymoon in Tehran : two years of love and danger in Iran - Moaveni, Azadeh, 1976- (New York : Random House, 2009)
The Iranian-American author describes her return to Iran as a reporter for'Time' magazine, her marriage to an Iranian man, the repressive Iranian society and its impact, and her family's decision to leave Iran.
Includes bibliographical references (p. [339]-340).
Keywords: Moaveni, Azadeh, -- 1976-; Ahmadinejad, Mahmoud; Moaveni, Azadeh, -- 1976- -- Marriage; Iranian American women -- Biography; Iranian Americans -- Biography; Women journalists -- Iran -- Biography; Women -- Iran -- Tehran -- Biography; Iran -- Politics and government -- 1997-; Iran -- Social conditions -- 1997-; Tehran (Iran) -- Biography